(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى معرفة سوء التوافق الجنسي وعلاقته بالتوافق الزواجي، وأيضاً، تعرّف الفروق بين أفراد العيّنة تبعاً لمتغيّرات (الجنس، المستوى التعليمي، والفئة العمرية)، وتم استخدام استبانة سوء التوافق الجنسي، واستبانة التوافق الزواجي من إعداد الباحثة، وقد طبقت الاستبانتان على عيّنة من (50) فرداً،25 زوجاً، و25 زوجة. وأظهرت النتائج: 1- أن هناك علاقة سلبية بين سوء التوافق الجنسي والتوافق الزواجي. 2- ظهرت فروق تبعاً لمتغيّر الجنس لصالح الذكور. 3- ولم تظهر فروق في سوء التوافق الجنسي تبعاً لمتغيّر المستوى التعليمي. 4- ولم تظهر فروق في سوء التوافق الجنسي تبعاً لمتغيّر الفئات العمرية لأفراد العيّنة. وجاء من توصيات البحث، إجراء بحوث لمعرفة المشكلات الجنسيّة التي تواجه الزوجين، وضرورة افتتاح مراكز علاج زواجية، تعتمد على الإرشاد، والعلاج للزوجين، متضمنّة العلاج، والإرشاد الجنسي. The objective of this research is to find the correlation between bad sexual adjustment and marriage adjustment. It also aims at studying the differences with regards to sex, education, and age. Two questionnaires were conducted on 50 couples: one for sexual intimacy and the other for marriage compatibility. The results showed: • No correlation between sexual incompatibility and marriage. • Differences based on sex variable in the benefit of males. • No differences in sexual incompatibility based on education variable. • No differences in sexual incompatibility based on age. The research recommends conducting further work to determine the sexual problems between couples. It also recommends opening marriage therapy centers that offer counseling and treatment including sexual counseling and treatment.